Mortalità per tumore maligno della pleura e casi indennizzati di malattie asbesto correlate nei comuni del Lazio (1980-2001) / Malignant pleural cancers mortality and compensated cases for asbestos related diseases in Lazio municipalities (1980-2001) - Scarselli, A.; Binazzi, A.; Altavista, et al., P. (La Medicina del Lavoro, 2007)
L’obiettivo di questo studio è di descrivere la distribuzione geografica nel Lazio delle patologie asbesto correlate per le quali esistono registrazioni correnti dei dati di lungo periodo (mortalità per tumore maligno della pleura e casi indennizzati di asbestosi) nel periodo 1980-2001 e di identificare le aree a maggior rischio. Per ciascun comune sono stati calcolati i rapporti standardizzati di mortalità (SMR) e di incidenza (SIR), rispettivamente per tumore maligno della pleura e per casi indennizzati di asbestosi, utilizzando i tassi specifici per sesso ed età della regione Lazio per stimare il numero dei casi “attesi”. Per l’identificazione dei cluster territoriali e la valutazione della loro significatività statistica è stato utilizzato il software SatScan. L’analisi conferma come aree a rischio per esposizione professionale la zona industriale di Colleferro e la zona portuale di Civitavecchia, con eccessi di mortalità per tumore maligno della pleura e di casi indennizzati per asbestosi. I risultati evidenziano la necessità della sorveglianza epidemiologica dei casi incidenti di mesotelioma maligno sull’intero territorio del Lazio e della ricostruzione delle modalità di esposizione ad amianto per ogni singolo caso, come strumento indispensabile per la prevenzione primaria di misconosciute esposizioni a fibre di amianto in ambito professionale, ambientale o residenziale. Malignant pleural cancers mortality and compensated cases for asbestos related diseases in Lazio municipalities (1980-2001) Background: Occupational exposure to asbestos has been widely reported in the Region, but a high risk for non-occupational and environmental contaminations have also been documented. Objectives: To describe the geographical distribution of pleural cancer deaths and compensated asbestosis cases from 1980 to 2001 in the Lazio Region. Methods: For each municipality Standardized Mortality Ratios (SMRs) for pleural cancer and Standardized Incidence Ratios (SIRs) for asbestosis were estimated. Expected cases were estimated from age and gender specific rates in Lazio. SatScan software was used to identify clusters and to verify their statistical significance. Results: 789 deaths from pleural cancer (495 males and 294 females) occurred in Lazio from 1980 to 2001. The standardized mortality rate per 100.000 inhabitants is 0,74 (0,95 for males and 0,54 for females). The main excess mortality from pleural cancer occurred in the municipalities of Civitavecchia (SMR: 269,9; 95% CI: 164,9 - 416,8), Colleferro (SMR: 304,9; 95% CI: 139,4-578,8) and Rocca Priora (SMR: 379,2; 95% CI: 103,3-970,9). Significant SIRs for compensated asbestosis cases were found in the industrial areas of the Naples-Rome highway and in the shipyard area of Civitavecchia. No female compensated cases were found. The most important clusters were identified in the municipality of Civitavecchia for pleural cancer (p-value = 0,117) and in the Colleferro industrial area for compensated asbestosis cases (p-value = 0,001). Conclusions: Epidemiological surveillance of incident cases of malignant mesothelioma in the Lazio Region and the investigation of modalities of asbestos exposure are urgently needed for prevention of occupational diseases.